Thinking about Religion - Smith, A. author. aut Link
X, 258 p.
Keywords: Thinking about Religion examines cutting-edge breakthroughs from across the sciences concluding that religion persists because the mind is primed for faith, ready to grasp and fiercely defend beliefs that make sense but defy logic.